Keterwakilan Politik Perempuan di Dewan Perwakilan Rakyat Republik Indonesia dalam Pemilu Tahun 2019 (Analisis Yuridis Terhadap Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum Dikaitkan dengan Perolehan Kursi Anggota Dewan Perempuan) - Daniswara, Vani Oviana; Riwanto, Agus (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis study aims to find out how far Law Number 7 of 2017 on General Elections has guaranteed the representation of women in the Indonesian Parliament in 2019 and what are the obstacles faced by women in the 2019 legislative elections. The results show that the representation of women in Indonesian Legislative Assembly seats had not reached 30% according to the UN minimum limit, due to many obstacles experienced by women in the 2019 election. The main obstacle experienced by many  women, include : (1) got cheated but doesn’t know how to report it; (2) financially incapable;  and (3) women only used as a complement to political party nomination quota. The way to achieve 30% representation that must be done is to reform Law Number 7 of 2017 concerning Elections. These reforms are carried out by adding articles or replacing articles so that in each electoral system, parties, nominations, campaigns, voting and vote counting have elements of affirmative action in them. Besides, a party nomination system is needed to be carried out openly.Keywords : women’s political representation; affirmative action; 2019 elections.